2019
DOI: 10.21608/jppp.2019.40553
|View full text |Cite
|
Sign up to set email alerts
|

Field Trials on Land Gastropods Infesting some Ornamental Plants at Kafr El-Sheikh Governorate

Abstract: Land molluscs became one of the most serious pests attacking many plants including ornamental plants. Occurrence of certain land gastropods associated with some ornamental plants at Kafr EL-Sheikh Governorate was conducted. Results revealed that the land snails, Eobania vermiculata and Succinea putris and the land slug Deroceras reticulatum were recorded on the tested plants. E vermiculata was the predominant species while the other identified gastropods showed lower infestation levels. Therefore ,the seasonal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…Theba pisana and E. vermiculata were the most abundant in all regions, while M. obstructa snails were found at relatively low population densities. Shahawy (2019)also reported that E. vermiculata was the predominant species in Kafr El-Sheikh governorate on ornamental plants and was recorded on all surveyed plants in relatively high numbers. However, the present data disagrees with that reported by Rady et al (2014), who stated that the M. cartusiana land snail was the predominant species in the fields of vegetable crops in the Ismailia and Sharkia governorates.…”
Section: Discussionmentioning
confidence: 98%
“…Theba pisana and E. vermiculata were the most abundant in all regions, while M. obstructa snails were found at relatively low population densities. Shahawy (2019)also reported that E. vermiculata was the predominant species in Kafr El-Sheikh governorate on ornamental plants and was recorded on all surveyed plants in relatively high numbers. However, the present data disagrees with that reported by Rady et al (2014), who stated that the M. cartusiana land snail was the predominant species in the fields of vegetable crops in the Ismailia and Sharkia governorates.…”
Section: Discussionmentioning
confidence: 98%
“…In the field trial carried out by Khidr (2019) in citrus orchards using methomyl, it was proved that the tested compound achieved a population reduction of E. vermiculata by 64.48 % and M. obstructa by 91.31%. Moreover, Shahawy (2019) revealed that Agrinate (methomyl 24 % W.P) was toxic to E vermiculata snails under field conditions, since it achieved the reduction percentage of snail population by 69 %. 2014) estimated the two application methods, spray and poisonous baits of methomyl against M. cartusiana and they indicated that the tested compound was practicable to reduce numbers of snails in Egyptian clover fields.…”
Section: Discussionmentioning
confidence: 99%
“…Singled out-that, the glassy clover snail, M. obstructa (Muller) which is the major species found infested wide range of crops at most localities of Egypt. Individuals of this species cause heavy damage to economically important crops (Abdel-Aal, 2007;El-Masry,1997;Mahrous et al, 2006;Lokma, 2007;Nakhla et al, 1995;Shahawy et al, 2008). These snails have active dispersal capabilities, which enable it to successfully expand its range to new habitats (El-Okda, 1981).…”
Section: Introductionmentioning
confidence: 99%